1984
DOI: 10.1126/science.6695183
|View full text |Cite
|
Sign up to set email alerts
|

Time-Varying Magnetic Fields: Effect on DNA Synthesis

Abstract: Human fibroblasts have exhibited enhanced DNA synthesis when exposed to sinusoidally varying magnetic fields for a wide range of frequencies (15 hertz to 4 kilohertz) and amplitudes (2.3 X 10(-6) to 5.6 X 10(-4) tesla). This effect, which is at maximum during the middle of the S phase of the cell cycle, appears to be independent of the time derivative of the magnetic field, suggesting an underlying mechanism other than Faraday's law. The threshold is estimated to be between 0.5 X 10(-5) and 2.5 X 10(-5) tesla … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
103
2
4

Year Published

1995
1995
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 342 publications
(110 citation statements)
references
References 13 publications
1
103
2
4
Order By: Relevance
“…Both the transient initial release of Ca 2+ from intracellular stores and the influx through specialized Ca 2+ channels operate the dephosphorylation of the cytoplasmic components (NFAT2 proteins) and give rise to their nuclear localization, which is followed by the activation of osteoclast-specific genes [6]. Pulsed electromagnetic fields (PEMFs) are useful therapy for patients with delayed fracture healing and nonunions [21] [22] [23] and affect different aspects of biomolecular synthesis in cells, including the kinetics of DNA, RNA, and protein production [24] [25]. In previous studies, research has focused of the effects of PEMF on osteoblasts and osteoclasts respectively, but the proliferation and activation of OC in OB-OC co-culture during PEMF stimulation has not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Both the transient initial release of Ca 2+ from intracellular stores and the influx through specialized Ca 2+ channels operate the dephosphorylation of the cytoplasmic components (NFAT2 proteins) and give rise to their nuclear localization, which is followed by the activation of osteoclast-specific genes [6]. Pulsed electromagnetic fields (PEMFs) are useful therapy for patients with delayed fracture healing and nonunions [21] [22] [23] and affect different aspects of biomolecular synthesis in cells, including the kinetics of DNA, RNA, and protein production [24] [25]. In previous studies, research has focused of the effects of PEMF on osteoblasts and osteoclasts respectively, but the proliferation and activation of OC in OB-OC co-culture during PEMF stimulation has not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…A study found PEMF affect only the osteoclast phenotype after short exposure times [42]. It has been determined that electric stimulation can enhance osteoblast differentiation [43], increase osteoblast proliferation and consequently increase bone formation [44,45]. The mechanism or PEMF to inhibit bone loss is not well understood.…”
Section: Figurementioning
confidence: 99%
“…As evidências biológicas disponíveis parecem indicar que sua ação se daria numa etapa mais tardia da carcinogênese, através de um efeito promotor ou co-promotor da doença 28,29,38,42,69,78 .…”
Section: Introductionunclassified